Insecticidal activity of crude ethanolic extracts of selected Philippine plants against diamondback moth, Plutella xylostella Linnaeus - Javier, Abigaile Mia V.; Ocampo, Virginia R.; Ceballo, Flor A.; Javier, Pio A. (2019)
The use of plant extracts could be an alternative method to the conventional insecticides for pest control. The potential of ethanolic extracts from Lantana camara Linnaeus, Coleus amboinicus Loureiro, Alpinia pyramidata Blume, Curcuma longa Linn., and Catharanthus roseus Linn. as insecticide against second larval instar diamondback moth?Plutella xylostella Linn.?was evaluated in the laboratory through contact and residual toxicities, antifeedant activity, repellency, and growth regulator activity. Among the five plants, L. camara was the most toxic against P. xylostella through topical application (LD50=99.17μg/g larva) and showed the highest antifeedant activity at 125μg/mL acetone. As demonstrated using leaf residue film method, Cu. longa was the most toxic against P. xylostella (LC50=206.22μg/mL) and also showed the highest repellency at 125μg/mL. Cu. longa and Ca. roseus exhibited high antifeedant activity at 500μg/mL. L. camara and A. pyramidata showed remarkable insect growth regulatory activities against P. xylostella. L. camara showed high larval and pupal mortalities, while A. pyramidata showed the highest number of abnormal adults produced. Among the ethanolic extracts, L. camara was the most promising because it consistently showed high contact toxicity plus antifeedant and remarkable insect growth regulatory activities against P. xylostella. Moreover, L. camara provided the highest ethanolic recovery (2.645%) among the test plants. In view of overall insecticidal potential of L. camara, can be exploited as a possible source of alternative insecticide against P. xylostella.
Includes bibliographical references (pages 41-43)
Keywords: Biology; Alpinia pyramidata; Antifeedant; Botanical insecticide; Catharanthus roseus; Curcuma longa; Lantana camara; Repellency